The Evolution of Nuclear Deterrence in South Asia - Yamin, Tughral (GHQ, Rawalpindi Services Book Club)
"This book is designed to build an informed opinion about nuclear deterrence in South Asia and its Cold War genesis. The aim is to generate an open minded debate among enthusiasts as well as professionals and to develop a deeper understanding of regional stability in the backdrop of nuclear deterrence"--Introduction.
Includes Bibliographical references and index.
Keywords: Military policy -- Nuclear warfare -- South Asia